Kompleksitas Perceraian Akibat Murtad: Analisis Peran Pengadilan Agama dalam Konteks Hukum Islam - Saputra, Maulana Adi; Widyawati, Silvia; Ardiyanto, Razi; Pitriana, Novia; Ramadhan, Agil Gilang (Indonesian Journal Publisher, 2024)
Divorce on grounds of apostasy is a complex research topic within Islamic law. This study explores the legal provisions of apostasy within the context of Islamic marriage law, with a focus on the role of the Religious Courts as dispute resolution institutions. The aim of this research is to investigate whether apostasy can constitute a valid basis for divorce according to the applicable law in the Religious Courts. The research method employed is a normative juridical approach to analyze the legal framework governing divorce cases involving apostasy. The research findings indicate that although apostasy can annul a marriage in religious terms, the Religious Courts do not always grant divorce without evidence of marital discord related to apostasy. This highlights the complexity of applying Islamic law in the context of divorce within the Religious Courts. Analysis of Article 116 (h) of the Compilation of Islamic Law regarding apostasy as a basis for divorce reveals that divorce is determined not only by religious conversion but also by the occurrence of marital discord resulting from apostasy. The implications of this discovery underscore the importance of a comprehensive understanding of Islamic law and contextual considerations in the process of resolving divorce disputes in the Religious Courts.